2009
DOI: 10.1063/1.3129842
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transitions in a two dimensional associating lattice gas model

Abstract: Monte Carlo simulation strategies for computing the wetting properties of fluids at geometrically rough surfaces J. Chem. Phys. 135, 184702 (2011) Semi-bottom-up coarse graining of water based on microscopic simulations J. Chem. Phys. 135, 184101 (2011) Hydrophobic interactions in presence of osmolytes urea and trimethylamine-N-oxide J. Chem. Phys. 135, 174501 (2011) Potential of mean force between identical charged nanoparticles immersed in a size-asymmetric monovalent electrolyte J. Chem. Phys. 135,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 20 publications
(18 reference statements)
3
32
1
Order By: Relevance
“…The critical line separating the fluid from the low density liquid phase, at lower pressures, could be associated to a fragile-to-strong transition, whereas the critical line separating the high density fluid from the HDL phase, at higher pressures, was associated to a strong-to-strong dynamic transition. 15 In both cases, the dynamic transition is of the same kind along the whole critical line. Thus, the dynamic transition upon traversing the critical line has been understood to be a result of the change of the structure of the liquid, similarly to the interpretation given to the dynamic transition seen in the case of the crossing of the Widom line.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The critical line separating the fluid from the low density liquid phase, at lower pressures, could be associated to a fragile-to-strong transition, whereas the critical line separating the high density fluid from the HDL phase, at higher pressures, was associated to a strong-to-strong dynamic transition. 15 In both cases, the dynamic transition is of the same kind along the whole critical line. Thus, the dynamic transition upon traversing the critical line has been understood to be a result of the change of the structure of the liquid, similarly to the interpretation given to the dynamic transition seen in the case of the crossing of the Widom line.…”
Section: Introductionmentioning
confidence: 93%
“…15,27 Second, we looked for dynamic transitions by analyzing the behavior of diffusivity with temperature across the critical line, at fixed chemical potentials. Our results showed that two different regimes may be found: If the critical line is crossed at low chemical potential, near the minimum in diffusivity, a fragile-to-strong transition is observed; for higher chemical potentials, near the diffusivity maximum, no dynamic transition is seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Even though there are a number of two and three dimensional lattice models that would in principle exhibit the anomalies present in water, 6,16,[19][20][21] here water is represented by the associating lattice gas (ALG) (Refs. [22][23][24][25][26][27][28]) that has already shown the density and diffusion anomalies described above. The ALG does not have the full complexity of the molecular liquid, however it leads to a network-forming fluid in which directionality plays an important role.…”
Section: Introductionmentioning
confidence: 99%